The influence of air gap length on the characteristics and performance of hybrid polyethersulfone/cellulose nanocrystal/multiwalled carbon nanotubes hollow fiber membrane for humic acid removal - Nor Azura, C. Mahmud; Syed Mohd Saufi, Tuan Chik; Mazrul Nizam, Abu Seman; Mohd Sobri, Takriff; Ang, Wei Lun; Mohd Helmi, Ab Latiff (John Wiley & Sons, 2024)
Ready-made or commercial hollow fiber (HF) membranes have limited performance for removing humic acid (HA) from water streams unless they undergo surface modification. Alternatively, a membrane can be tailor-made specifically for HA removal by developing a new formulation and adjusting its fabrication parameters. In this study, to enhance the performance and antifouling properties of HF membranes, a hybrid membrane was developed by blending polyethersulfone (PES) with cellulose nanocrystals (CNC) and multiwalled carbon nanotubes (MWCNT). The effect of air gap length during the dry–wet spinning process was investigated, ranging from 3 cm to 12 cm, to regulate the properties of the hybrid membrane. The membranes were evaluated in terms of morphology (FESEM and AFM), porosity, and hydrophilicity (contact angle). Water flux, HA rejection, and flux recovery ratio (FRR) were also measured. The air gap length significantly influenced the fiber structure, with the finger-like structure expanding from the outer surface to the center of the fiber as the air gap extended up to 9 cm. This increase in air gap length resulted in a significant reduction in porosity, decreasing from 75.59% to 43.45%, while simultaneously enhancing the contact angle from 78° to 89.60°. The membrane produced at a 9 cm air gap length exhibited the best performance, with a pure water flux of 15.83 LMH, HA rejection over 95%, and a high FRR of 98.78%. The synergistic effect of combining CNC with MWCNT and simply adjusting the air gap distance proves to be an effective approach for preparing custom-made HF membranes for HA removal.